PENDAFTARAN INDIKASI GEOGRAFIS ATAS BARANG-BARANG HASIL PERTANIAN/PERKEBUNAN DI ACEH - PUJI TRI NUZZULI (PREMISE LAW JURNAL, 2015)
Allah has endowed grace to the Acehnese with abundant agricultural products which haves pecific quality. Aceh has various natural resources with abundant agricultural products such as Kopi Gayo, nutmegs, patchouli, pepper, clover, Kopi Ulee Kareng, and Pisang Siem. Agricultural products in each area also have their specific or special characteristics which become its superior quality such as their aroma, taste, color, size, and texture so that they can compete with other products of the same types. Existence of Goods have potency to be protected by the geographical indication at Aceh society in Aceh. Governmental during the time have given a[n action which are positive in registering of a[n geographical indication typically Aceh society. Local government after registering of the geographical indication only evaluating one year once local society existence and plantation copy the people, monitoring or perception of only by On duty Plantation in Provinsi Aceh to see how far growth, sale and labialization from this Coffee Gayo. geographical Indication registration to the goods owning to have potency to be registered by a geographical indication in Aceh, Applicant apply to Directorate of Brand of Intellectual Equity General Directorate (HKI) in Banda Aceh which will be by a formality inspection (14 day) [done/conducted] [by] inspection substantive (2 year), agreed to be enlisted (10 day) Announcement ( 3 month) otherwise there [is] opposition IG enlisted. Keywords : Registration for Geographical Indication, Agricultural/Plantation Products